Hidden Companions to Intermediate-mass Stars. X. Solving for the Mass Ratio in the Spectroscopic Binary Zubenelgenubi = α 2 Librae - Waisberg, Idel; Klein, Ygal; Katz, Boaz (Research notes of the AAS, 2023)
Zubenelgenubi = α 2 Librae is a nearby double-lined spectroscopic binary that forms a quadruple system with α 1 Librae. The radial velocity amplitude for the rapidly rotating primary is subject to a systematic uncertainty and as a result only a lower limit q = 0.81 to the mass ratio has been previously reported. Here we present a VLTI/GRAVITY interferometric observation of Zubenelgenubi in which we measured a K band flux ratio of 74.7%, resulting in isochrone masses M Aa = 1.95 M ⊙ and M Ab = 1.79 M ⊙ ( q = 0.92). The fact that the projected rotational velocities differ by a factor of three despite the similar masses suggests that the stellar spin axes are significantly misaligned in spite of the small semimajor axis a = 0.52 au or alternatively that the primary is a merger product.